The Potential of Halal Tourism System on Growth for the Province Lampung's Tourism Industry - SURYANTO, Tulus; HAYATI, Mardhiyah; SUSANTI, Yeni (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The implementation of Sharia tourism in Indonesia is still new, including in the province Lampung with the tourism position!!! market strategy “the treasure of Sumatera.” This research aims to identify the defining factors of the halal tourism system’s potential for the tourism industry growth in Lampung Province. This study took into consideration four tourism places: Pantai Pasir Putih – South Lampung, Taman Nasional Way Kambas – East Lampung, Masjid Terapung Al-Aminah – Pantai Sari Ringgung – Pesawaran, Lembah Hijau – Bandar Lampung and involved 120 respondents, including managers, workers and consumers. The results showed there were some defining factors of the potential of the halal tourism system in the Lampung Province, like the religious facilities which follow the sharia’s principles, easily affordable and suitable for usage; the halal foods and beverages with certificate MUI halal, also the cleanliness, the nature preservation, sanitation and environment been widely shown.